Analisis Pengajuan Masalah Dalam Pembelajaran Matematika Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Ivonny Melati Prihandini; Kunti Dian Ayu Afiani; Badruli Martati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
The purpose of this study was to analyze the problem posed in mathematics learning which can improve the creative thinking skills of elementary school students. This research is a type of qualitative research using the literature study method. Where the data sources used in this study are journals related to problem posing to improve students' creative thinking skills. Based on the results of the analysis that has been carried out, it can be concluded that learning based on submission of this problem can be increased significantly because the abilities possessed by students have been well honed with an average value of 31,35%. This can be seen from the results of students before and after treatment in the classroom. Problem posing-based learning can not only improve the results of creative thinking skills, but students can also understand how the concepts in problem-based learning properly and correctly, because the concepts used must have the right techniques and strategies.